Macroprudential Policy Spillovers : A Quantitative Analysis - Kang, Heedon (IMF Working Papers; Working Paper, 2017)
This paper analyzes cross-border macrofinancial spillovers from a variety of macroprudential policy measures, using a range of quantitative methods. Event study and panel regression analyses find that liquidity and sectoral macroprudential policy measures often affect cross-border bank credit, whereas capital measures do not. This empirical evidence is stronger for tightening than for loosening measures, is distributed across credit leakage and reallocation effects, and is generally regionally concentrated. Consistently, structural model based simulation analysis indicates that output and bank credit spillovers from sectoral macroprudential policy shocks are generally small worldwide, but are regionally concentrated and economically significant for countries connected by strong trade or financial linkages. This simulation analysis also indicates that countercyclical capital buffer adjustments have the potential to generate sizeable regional spillovers.